The Palgrave Handbook of Global Politics in the 22nd Century - Horn, Laura; Mert, Ayşem; Müller, Franziska (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
XI, 437 p. 29 illus., 9 illus. in color.